Modelling and Forecasting the Kuala Lumpur Composite Index Rate of Returns Using Generalised Autoregressive Conditional Heteroscedasticity Models - Abdul Muthalib, Maiyastri (2004)
The work in this thesis is concerned with the modelling and forecasting of the KLCI’s returns with a ‘complete’ technique. The selection of the model for estimation is not only based on the value of the goodness of fit test, but also on the test of the stability of parameters obtained, the checking of the characteristic of the standardized residual such as the ARCH-LM test, Ljung-Box test, asymmetry test (SB, NSB, and PSB test). Its distribution is examined by qq-plot. The forecasting is carried out by using the multi-step-ahead forecast.